Dehydroepiandrosterone sulfate to cortisol ratio as a prognostic factor in cirrhotic patients with spontaneous bacterial peritonitis - Mohamed Ramadan Asker; Loai Mohamed Elahwal; Sahar Mohy-Eldin Hazzaa; Shireen Ali Elhoseeny; Mohamed Elsayed Sarhan (SpringerOpen, 2023)
Abstract Background Chronic liver disease and decompensated cirrhosis are associated with serious complications; spontaneous bacterial peritonitis is considered one of them that may lead to sepsis and adrenal insufficiency. This trial aimed to study the role of dehydroepiandrosterone sulfate (DHEAS) and DHEAS/cortisol ratio for assessing cirrhotic patients' adrenal function and as a possible prognostic factor in cirrhotic cases with spontaneous bacterial peritonitis (SBP). Patients and methods It was a prospective cohort trial carried out on 100 patients in the Internal Medicine Department, Tanta University Hospital, from June 2021 to July 2022 divided into 2 studied patient groups: group I, 50 cases with liver cirrhosis and sterile ascites; and group II, 50 cases with liver cirrhosis and SBP. Adrenal function was evaluated using serum cortisol levels (9 A.M, 9 P.M, and post synacthen stimulation test), DHEAS level, and DHEAS/cortisol ratio. Results The cirrhotic patients with SBP have significantly decreased DHEAS, decreased DHEAS/cortisol ratio, and high cortisol level post stimulation compared with patients with sterile ascites, cirrhotic cases with decreased DHEAS/cortisol ratio (< 0.65) had elevated C-reactive protein (CRP) levels, a higher model for end-stage liver disease (MELD) score and Child-Pugh score had higher hospital mortality. Both DHEAS and the DHEAS/cortisol ratio were significant predictors of hospital mortality (area under the receiver operating characteristic curve 0.267 and 0.298, respectively). The cirrhotic patients with SBP had decreased DHEAS and DHEAS/cortisol ratio but higher hospital mortality, compared to the cirrhotic patients with sterile ascites. Conclusions It was found that a significant increase in cortisol level was after synacthen stimulation, decreased DHEAS, and low DHEAS to cortisol ratio in the cirrhotic patients with spontaneous bacterial peritonitis and was associated with high mortality compared to cirrhotic patients without spontaneous bacterial peritonitis.